Preparation method and application of heteroatom coordination modified biomass-based hard carbon material
Through the preparation method of biomass-based hard carbon material modified with heteroatom coordination, the problem of hysteresis of biomass-based hard carbon material in sodium ion batteries and low first-circle Coulomb efficiency is solved, and a higher reversible sodium storage capacity and higher Coulomb efficiency are achieved.
Patent Information
- Application Number
- CN202411880481.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-04-29
AI Technical Summary
The sodium storage performance of existing biomass-based hard carbon materials in sodium ion batteries is lagging behind, and the first-circle Coulomb efficiency is low due to internal defects, which increases the battery usage cost.
The preparation method of biomass-based hard carbon material modified by heteroatom coordination is adopted, and the internal structure and electron cloud distribution of the material are adjusted through pre-carbonization, salt solution impregnation, freeze-drying and high-temperature carbonization.
It significantly improves the reversible capacity of sodium storage of biomass-based hard carbon materials and the first-circle Coulomb efficiency, improves the performance of sodium ion batteries, and reduces production costs.
Smart Images

Figure CN119898748A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of sodium ion batteries, and specifically relates to a preparation method and application of a heteroatom coordinated modified biomass-based hard carbon material. Background Art
[0002] As a new generation of high energy density energy storage devices, sodium ion batteries have the most potential for commercialization as their negative electrode hard carbon, which has the advantages of low voltage platform, high capacity, good cycle stability, and abundant raw material sources. Using biomass (straw, bamboo, wood, etc.) as the raw material for hard carbon synthesis can not only promote the development and utilization of agricultural and forestry biomass energy, accelerate the construction of a waste recycling system, but also greatly reduce production costs, reduce environmental pollution and carbon emissions, and achieve low-carbon transformation.
[0003] However, at present, the sodium storage performance of bio-based hard carbon prepared with biomass as raw material still has a large hysteresis phenomenon, and cannot perfectly match the performance of the positive electrode material in sodium ion. In addition, biomass-based hard carbon often has a low first-cycle coulomb efficiency in sodium-ion batteries due to the presence of many defects inside the material, which will greatly increase the cost of the positive electrode and electrolyte in the commercial application of sodium-ion batteries. At present, in many hard carbon material research reports, the use of heteroatom doping is considered to be an effective way to improve the electrochemical performance of hard carbon negative electrode materials for sodium-ion batteries, but heteroatom doping often brings too many defects, which will reduce its first-cycle coulomb efficiency while improving the performance of hard carbon. Therefore, while improving the performance of hard carbon by doping, ensuring that its defect content remains stable so that it still maintains a high first-cycle coulomb efficiency is an urgent problem to be solved in this field. Summary of the invention
[0004] In view of the problems and shortcomings of the prior art, the present invention aims to provide a method for preparing and applying a biomass-based hard carbon material modified by heteroatom coordination.
[0005] According to one aspect of the present invention, there is provided a method for preparing a heteroatom-coordinated modified biomass-based hard carbon material, which comprises the following specific steps:
[0006] (1) Raw material selection: biomass raw materials;
[0007] (2) Raw material pre-carbonization: pre-carbonizing the biomass raw material;
[0008] (3) Raw material grinding: grinding and crushing the pre-carbonized product obtained in step (2);
[0009] (4) Powder modification: the ground powder obtained in step (3) is immersed in a salt solution and stirred, and then freeze-dried to obtain a modified powder raw material;
[0010] (5) High-temperature carbonization: The modified powder raw material obtained in step (4) is subjected to high-temperature carbonization, and then the carbonized hard carbon powder is acid-washed to obtain the heteroatom-coordinated modified biomass-based hard carbon material.
[0011] According to some embodiments of the present application, the biomass raw material is at least one of woody biomass raw materials such as beech, eucalyptus, pine, balsa wood, birch, and poplar; preferably, it is beech.
[0012] According to some embodiments of the present application, the biomass raw materials are subjected to a simple water washing, acid washing, and water washing process at one time to ensure the purity of the raw materials.
[0013] According to some embodiments of the present application, the pre-carbonization temperature is 200-600°C, the pre-carbonization time is 1-6h, and the pre-carbonization atmosphere is one of an oxygen-free environment, nitrogen, and argon; preferably, the atmosphere is nitrogen, the pre-carbonization temperature is 400-600°C, and the pre-carbonization time is 4-6h.
[0014] According to some embodiments of the present application, the mesh number of the raw material after grinding is between 50-300 meshes, preferably 100 meshes.
[0015] According to some embodiments of the present application, the salt solution is at least one of ammonium phosphate, ammonium sulfate, ammonium borate, ammonium chloride, ammonium oxalate, urea, and thiourea, preferably at least one of ammonium phosphate, ammonium sulfate, ammonium borate, and ammonium chloride.
[0016] According to some embodiments of the present application, the concentration of the salt solution is 0.1-5 mol / L, for example, 0.1 mol / L, 0.5 mol / L, 1.0 mol / L, 2.0 mol / L, 5 mol / L, preferably 1 mol / L.
[0017] According to some embodiments of the present application, the impregnation method is hot liquid immersion, the immersion temperature is 25-80°C, the immersion time is 1-12h, and the immersion solid-liquid ratio (g / mL) is 1:1-1:5; preferably, the immersion temperature is 40°C and the immersion time is 4-6h.
[0018] According to some embodiments of the present application, the freeze drying is performed in a corresponding instrument, which completely removes water while greatly retaining the solute salt in the internal pores of the modified powdered carbon.
[0019] According to some embodiments of the present application, the high-temperature carbonization temperature is 1200-1500°C, the carbonization time is 2-6h, and the carbonization atmosphere is one or more of nitrogen and argon; preferably, the high-temperature carbonization temperature is 1300°C, and the carbonization time is 3h.
[0020] According to some embodiments of the present application, the pickling solution is a hydrochloric acid solution, a sulfuric acid solution, or a nitric acid solution, and preferably the pickling solution is a hydrochloric acid solution.
[0021] Another object of the present invention is to provide a biomass-based hard carbon material modified by heteroatom coordination prepared by the above preparation method. The material is nitrogen-sulfur coordination modified, nitrogen-phosphorus coordination modified, nitrogen-chlorine coordination modified or nitrogen-boron coordination modified.
[0022] Another object of the present invention is to provide a sodium ion battery hard carbon electrode, using the above-mentioned heteroatom coordinated modified biomass-based hard carbon material, using aluminum foil as a current collector, conductive carbon (super P) as a conductive agent, and carboxymethyl cellulose (CMC) as a binder.
[0023] The present invention also provides a sodium ion battery half-cell testing device, which uses the above-mentioned sodium ion battery hard carbon pole piece, uses a sodium sheet as a counter electrode, GF / F as a diaphragm, and sodium hexafluorophosphate as an electrolyte to assemble in a C2032 stainless steel battery shell to prepare a sodium ion battery half-cell testing device.
[0024] Compared with the prior art, the technical features and advantages of the present invention are as follows:
[0025] The present invention provides a method for preparing a biomass-based hard carbon material modified by heteroatom coordination. At the same time, beech and other biomass are used as raw materials, and are modified through simple pre-carbonization, salt impregnation, freeze-drying and other processes to prepare biomass hard carbon materials modified by different heteroatom coordination.
[0026] In terms of modification, the present invention innovatively combines hydrothermal impregnation with freeze drying. First, the salt solution is fully absorbed by hydrothermal immersion, so that the pores are filled with the modified salt solution. Then, further freeze drying is performed to remove water while retaining the solid salt inside the modified powder material to a great extent. It further volatilizes during the subsequent high-temperature carbonization process, thereby changing the structure and electron cloud distribution of the microcrystalline graphite layer inside the hard carbon material to a greater extent.
[0027] The heteroatom coordination-modified biomass-based hard carbon material prepared by the present invention adjusts the adsorption and migration capabilities of the biomass hard carbon for sodium ions due to the presence of heteroatom coordination such as nitrogen-sulfur, nitrogen-phosphorus, nitrogen-chlorine, and nitrogen-boron, greatly improving its reversible capacity for sodium storage, making it have higher performance and practical application potential in the carbon-based negative electrode of sodium ion batteries.
[0028] The heteroatom coordinated modified biomass-based hard carbon material of the present invention uses beech and other biomass as raw materials, which are widely available and environmentally friendly. Meanwhile, the production process is simple, the carbon emission is low, the yield is high, and the potential for long-term industrial application is high. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 These are SEM images of the hard carbon materials prepared in Examples 1-4 of the present invention and Comparative Example 1.
[0030] Figure 2 Raman graphs of the hard carbon materials prepared in Examples 1-4 of the present invention and Comparative Example 1.
[0031] Figure 3 XRD diagrams of the hard carbon materials prepared in Examples 1-4 and Comparative Example 1 of the present invention.
[0032] Figure 4 This is a rate performance diagram of the hard carbon materials prepared in Examples 1-4 and Comparative Example 1. DETAILED DESCRIPTION
[0033] The technical solution of the present invention is further described below in conjunction with specific embodiments, but the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present application.
[0034] The present invention is described in detail below
[0035] A method for preparing a heteroatom-coordinated modified biomass-based hard carbon material comprises the following steps:
[0036] (1) Raw material selection: biomass raw materials;
[0037] (2) Raw material pre-carbonization: The biomass raw materials are placed in a large atmosphere furnace for pre-carbonization;
[0038] (3) Raw material grinding: grinding and crushing the pre-carbonized product obtained in step (2);
[0039] (4) Powder modification: the ground powder obtained in step (3) is immersed in a salt solution and stirred, and then freeze-dried to obtain a modified powder raw material;
[0040] (5) High-temperature carbonization: The modified powder raw material obtained in step (4) is placed in a large atmosphere furnace for high-temperature carbonization, and then the carbonized hard carbon powder is acid-washed to obtain the heteroatom-coordinated modified biomass-based hard carbon material.
[0041] Example 1
[0042] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0043] Example 2
[0044] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium sulfate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-sulfur coordination-modified biomass hard carbon material by acid washing and drying.
[0045] Example 3
[0046] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium chloride solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-chlorine coordination-modified biomass hard carbon material by acid washing and drying.
[0047] Example 4
[0048] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium borate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-boron coordination-modified biomass hard carbon material by acid washing and drying.
[0049] Example 5
[0050] Weigh 100g of cleaned eucalyptus raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0051] Example 6
[0052] Weigh 100g of cleaned balsa wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0053] Example 7
[0054] Weigh 100g of cleaned bamboo powder raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0055] Comparative Example 1
[0056] 100 g of cleaned beech wood raw material was weighed and placed in an atmosphere furnace, pre-carbonized at 500 ° C for 4 h in a nitrogen atmosphere, and the pre-carbonized raw material was crushed evenly and placed in an aqueous solution, and soaked and stirred at 40 ° C for 6 h. The raw material powder was then freeze-dried, and further placed in an atmosphere furnace at 1300 ° C, carbonized in a nitrogen atmosphere for 3 h, and finally acid-washed and dried to obtain an unmodified biomass hard carbon material.
[0057] Comparative Example 2
[0058] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 300℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0059] Comparative Example 3
[0060] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 12h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0061] Comparative Example 4
[0062] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1200℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0063] Comparative Example 5
[0064] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then freeze-dry the raw material powder, further place it in an atmosphere furnace at 1400℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0065] Comparative Example 6
[0066] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then filter and extract the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-phosphorus coordination-modified biomass hard carbon material by acid washing and drying.
[0067] Comparative Example 7
[0068] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium sulfate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then filter and extract the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-sulfur coordination-modified biomass hard carbon material by acid washing and drying.
[0069] Comparative Example 8
[0070] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium chloride solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then filter and extract the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-chlorine coordination-modified biomass hard carbon material by acid washing and drying.
[0071] Comparative Example 9
[0072] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium borate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then filter and extract the raw material powder, further place it in an atmosphere furnace at 1300℃, carbonize it in a nitrogen atmosphere for 3h, and finally obtain the nitrogen-boron coordination modified biomass hard carbon material by acid washing and drying.
[0073] Comparative Example 10
[0074] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium phosphate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then the raw material powder is vacuum dried, further placed in an atmosphere furnace at 1300℃, carbonized for 3h in a nitrogen atmosphere, and finally washed and dried by acid to obtain a nitrogen-phosphorus coordination-modified biomass hard carbon material.
[0075] Comparative Example 11
[0076] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium sulfate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then the raw material powder is vacuum dried, further placed in an atmosphere furnace at 1300℃, carbonized for 3h in a nitrogen atmosphere, and finally washed and dried by acid to obtain a nitrogen-sulfur coordination-modified biomass hard carbon material.
[0077] Comparative Example 12
[0078] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium chloride solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then the raw material powder is vacuum dried, further placed in an atmosphere furnace at 1300℃, carbonized for 3h in a nitrogen atmosphere, and finally washed and dried by acid to obtain a nitrogen-chlorine coordinated modified biomass hard carbon material.
[0079] Comparative Example 13
[0080] Weigh 100g of cleaned beech wood raw material, place it in an atmosphere furnace, pre-carbonize it at 500℃ in a nitrogen atmosphere for 4h, crush the pre-carbonized raw material evenly, and place it in a 1mol / L ammonium borate solution (solid-liquid ratio 1:2g / mL), soak and stir it at 40℃ for 6h. Then the raw material powder is vacuum dried, further placed in an atmosphere furnace at 1300℃, carbonized for 3h in a nitrogen atmosphere, and finally washed and dried by acid to obtain a nitrogen-boron coordination-modified biomass hard carbon material.
[0081] Sodium storage performance test
[0082] The biomass hard carbon materials prepared in the above embodiments and comparative examples were prepared into negative electrode slurry in a mass ratio of hard carbon: conductive agent: binder (9:0.5:0.5), and coated on the current collector (copper foil). The slurry was then dried and sliced, and C2032 button batteries were assembled in a glove box. After standing for 12 hours, they were placed in the Xinwei battery test channel for relevant sodium storage performance tests.
[0083] Figure 1 The SEM images of the hard carbon materials prepared in Examples 1-4 of the present invention and Comparative Example 1. It can be seen that the biomass hard carbon materials modified by nitrogen-sulfur, nitrogen-phosphorus, nitrogen-chlorine, and nitrogen-boron coordination prepared by the present invention have disordered particle morphology, which is similar to the hard carbon morphology prepared from native biomass, indicating that the modification process in the present invention will not significantly change the surface morphology structure of the hard carbon.
[0084] Figure 2 The Raman graphs of the hard carbon materials prepared in Examples 1-4 and Comparative Example 1 of the present invention are shown in FIG. Figure 3 From the calculation of ID / IG, it can be seen that the nitrogen-sulfur, nitrogen-phosphorus, nitrogen-chlorine, and nitrogen-boron coordination-modified biomass hard carbon materials prepared in Examples 1-4 all have a peak area ratio of 1.5. This moderate degree of graphitization can ensure that the introduction of heteroatom coordination will not significantly reduce the irreversible sodium ion adsorption in the first cycle of charge and discharge.
[0085] Figure 3 The XRD diagrams of the hard carbon materials prepared in Examples 1-4 of the present invention and Comparative Example 1. From the XRD, it can be seen that characteristic diffraction peaks of amorphous carbon are displayed near 22.5° and 43.5°, which correspond to the (002) and (100) crystal planes of the graphite region in the hard carbon, respectively, and the 002 peak of Examples 1-4 has not shifted significantly, indicating that the coordination modification of nitrogen-sulfur, nitrogen-phosphorus, nitrogen-chlorine, and nitrogen-boron is to regulate the adsorption, migration and diffusion capacity of the carbon layer for sodium ions, and will not significantly change the graphite microcrystalline region structure of the hard carbon.
[0086] Figure 4 The figure is a rate performance diagram of the hard carbon material prepared in Examples 1-4 and Comparative Example 1. Figure 4 It can be seen that the biomass hard carbon materials modified by nitrogen-sulfur, nitrogen-phosphorus, nitrogen-chlorine and nitrogen-boron coordination have significantly improved the sodium ion reversible capacity at different current densities compared with the unmodified biomass hard carbon materials (Comparative Example 1). Among them, the nitrogen-phosphorus coordination modified hard carbon material prepared in Example 1 has a reversible capacity of 396.3 mAh / g and an ultra-high first-cycle coulombic efficiency of 89.1%, indicating that the biomass hard carbon material prepared by heteroatom coordination modification in the present invention has more excellent sodium storage performance and application potential.
[0087] By further comparing the powder modification processes in Examples 1-4 and Comparative Examples 6-13, it can be seen that the modification method innovatively adopted by the present invention, which combines hot liquid impregnation and freeze-drying, can achieve a greater degree of salt retention than conventional filtration extraction and vacuum drying under the same salt solution impregnation concentration and carbonization procedure, thereby greatly improving the efficiency of coordination modification and the performance of biomass-based hard carbon.
[0088] The test data of the embodiments and comparative examples are shown in the following table:
[0089]
[0090]
[0091] The description of the above embodiments is only used to help understand the method and core idea of the present application. It should be pointed out that for ordinary technicians in this technical field, any changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a heteroatom-coordinated modified biomass-based hard carbon material, characterized in that: The steps include: (1) pre-carbonizing the biomass raw material; (2) grinding and crushing the pre-carbonized product obtained in step (1); (3) immersing and stirring the ground powder obtained in step (2) in a salt solution, and then freeze-drying to obtain a modified powder raw material; (4) The modified powder raw material obtained in step (3) is subjected to high-temperature carbonization, and then the carbonized hard carbon powder is acid-washed to obtain the heteroatom-coordinated modified biomass-based hard carbon material.
2. The preparation method according to claim 1, characterized in that: In step (1), the biomass raw material is at least one of beech, eucalyptus, pine, balsa wood, birch and poplar.
3. The preparation method according to claim 1, characterized in that: In step (1), the pre-carbonization temperature is 200-600° C., the pre-carbonization time is 1-6 hours, and the pre-carbonization atmosphere is one of an oxygen-free environment, nitrogen, and argon.
4. The preparation method according to claim 1, characterized in that: In step (3), the salt solution is at least one of ammonium phosphate, ammonium sulfate, ammonium borate, ammonium chloride, ammonium oxalate, urea, and thiourea.
5. The preparation method according to claim 1, characterized in that: In step (3), the concentration of the salt solution is 0.1 to 5 mol / L, preferably 1 mol / L.
6. The preparation method according to claim 1, characterized in that: In step (3), the immersion method is hot liquid immersion, the immersion temperature is 25-80°C, the immersion time is 1-12h, and the immersion solid-liquid ratio is 1:1-1:5g / mL; preferably, the immersion temperature is 40°C and the immersion time is 4h.
7. The preparation method according to claim 1, characterized in that: In step (4), the high temperature carbonization temperature is 1200-1500° C., the carbonization time is 2-6 hours, and the carbonization atmosphere is one or more of nitrogen and argon.
8. The preparation method according to claim 1, characterized in that: In step (4), the pickling solution is one of hydrochloric acid solution, sulfuric acid solution and nitric acid solution.
9. A biomass-based hard carbon material modified by heteroatom coordination, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. The use of the heteroatom coordinated modified biomass-based hard carbon material according to claim 9, characterized in that: The heteroatom coordinated modified biomass-based hard carbon material is used to prepare a sodium ion battery hard carbon pole piece or a sodium ion battery half-cell testing device.
Citation Information
Patent Citations
Pyrolysis hard carbon material with longitudinal pore structure and preparation method and application thereof
CN108315028A
Biomass hard carbon negative electrode material of sodium ion battery and preparation method of biomass hard carbon negative electrode material
CN113206246A
Preparation method of nitrogen and phosphorus co-doped biomass derived capacitive deionization electrode
CN113880086A
Biomass-based sodium ion hard carbon negative electrode material with low cost and high performance
CN119050352A